Evaluation of feasibility of medial plantar artery flap with computed tomography angiography in diabetic patients: a pilot radioanatomic study - Ahmad Alwi, Akmal Azim; Low, Chooi Leng; Kow, Ren Yi; Tajudin, Fatin Azreen; Lim, Bee Chiu; Halim Lim, Aidi Aswadi; Md Ralib @ Md Raghib, Ahmad Razali (Springer Nature, 2023)
Background: A soft tissue defect resulting from a diabetic heel ulcer can be difficult to address due to limited reconstructive options and unique local area demand. The medial plantar artery flap is ideal for heel defect coverage as it provides a thick glabrous skin with good sensory feedback. The prerequisite of medial plantar artery flap surgery is a patent medial plantar artery, which is a branch of the posterior tibial artery (PTA). Nevertheless, no feasibility study of the medial plantar artery flap in diabetic patients with vascular insufficiency has been reported so far. We conducted a pilot study with the aim of investigating the patency of the medial plantar artery in diabetic patients with suspected peripheral artery disease to determine the vascular feasibility of the medial plantar artery flap in these patients.